Energy-generating potential of anaerobically enhanced primary treatment of domestic wastewater using multiple-compartment bioreactors. Issue 1 (12th November 2019) - Pfluger, Andrew; Erickson, Rebecca; Vanzin, Gary; Hahn, Martha; Callahan, Jennie; Munakata-Marr, Junko; Figueroa, Linda
Abstract : Modeled electrical energy generation from anaerobic primary treatment of domestic wastewater with baffled bioreactors. Energy generation from methane production exceeded energy use by conventional activated sludge in some scenarios. Abstract : Wastewater reclamation facilities have the potential to be net energy producers if anaerobic bioreactors coupled with energy-generating technologies, such as combined heat and power (CHP), are employed. To characterize the energy-generating potential of multiple-compartment anaerobic bioreactors used for enhanced primary treatment of domestic wastewater, organic removal and observed methane (CH4 ) generation from two pilot-scale anaerobic baffled bioreactors operating for more than 2400 days over a range of wastewater temperatures (11 to 24 °C) were characterized. Aggregated data from both bioreactor systems were subjected to uncertainty analysis and modeling to increase confidence in results and to determine the energy-generating potential from five different CHP technologies. Results suggest that multiple-compartment anaerobic reactors converted 76% of the chemical oxygen demand (COD) removed to methane-rich biogas (effective energy content of 2.0 kW h kg −1 COD removed). Observed CH4 production was most accurately modeled using total COD measurements, not biodegradable COD estimates. The use of the aerobic biochemical oxygen demand (BOD) assay underestimated the amount of anaerobically biodegradable COD. Modeled scenarios suggest that energy generated from several CHP technologies with heat recovery ( i.e., effective electrical energy) can provide power equivalent to the amount used by many conventional activated sludge systems. A modeled future scenario where dissolved methane (dCH4 ) is recovered for energy generation also suggests that dCH4 capture provides additional energy generation and is needed to reduce greenhouse gas emissions. Based on COD, mass balances indicate that using multiple-compartment anaerobic reactors for anaerobically enhanced primary treatment increases the portion of COD in the influent wastewater going to electrical energy from ∼8.5% to 21%. Results from this study suggest that replacing conventional primary treatment with anaerobic bioreactors can enhance energy-generating potential at water resource recovery facilities.